Pengukuran Capability Level Kualitas Layanan E-Government Kabupaten Pamekasan Menggunakan Framework COBIT 5.0 - Darmawan, Aang Kisnu; Dwiharto, Arisandi (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2019)
This study aims to conduct an audit and evaluation of the Pamekasan District e-Government Dispute Settlement services on EDM and APO Domains. The method used is the COBIT Framework.5, a framework for measuring information system governance maturity issued by ISACA in 2012. The audit was conducted at the Pamekasan District Dispendukcapil Office and took samples of e-Government Services in 4 Districts and 12 Districts considered quite representative to be audited.The results showed that overall the results of the audit capability level of ICT services at Pamekasan district Dispendukcapil were at level 3 (Establish) with capability level index values in establish and 2.O (established) EDM domains. Field findings show that business processes in ICT management of e-government services at the sub-district, village levels show that they are at level 0 (incomplete), which means that there is almost no process of governance of ICT services at that level. Suggestions and recommendations that can be made are more authority is needed at the sub-district and village level by adding competent human resources in the ICT field to provide better e-Government services.